The Excitatory Effects of GABA within the Suprachiasmatic Nucleus: Regulation of Na-K-2Cl Cotransporters (NKCCs) by Environmental Lighting Conditions - McNeill, John K. (J Biol Rhythms, 2020)
The suprachiasmatic nucleus (SCN) contains a pacemaker that generates circadian rhythms and entrains them with the 24-h light-dark cycle (LD). The SCN is composed of 16,000 to 20,000 heterogeneous neurons in bilaterally paired nuclei. γ-amino butyric acid (GABA) is the primary neurochemical signal within the SCN and plays a key role in regulating circadian function. While GABA is the primary inhibitory neurotransmitter in the brain, there is now evidence that GABA can also exert excitatory effects in the adult brain. Cation chloride cotransporters determine the effects of GABA on chloride equilibrium, thereby determining whether GABA produces hyperpolarizing or depolarizing actions following activation of GABA(A) receptors. The activity of Na-K-2Cl cotransporter1 (NKCC1), the most prevalent chloride influx cotransporter isoform in the brain, plays a critical role in determining whether GABA has depolarizing effects. In the present study, we tested the hypothesis that NKCC1 protein expression in the SCN is regulated by environmental lighting and displays daily and circadian changes in the intact circadian system of the Syrian hamster. In hamsters housed in constant light (LL), the overall NKCC1 immunoreactivity (NKCC1-ir) in the SCN was significantly greater than in hamsters housed in LD or constant darkness (DD), although NKCC1 protein levels in the SCN were not different between hamsters housed in LD and DD. In hamsters housed in LD cycles, no differences in NKCC1-ir within the SCN were observed over the 24-h cycle. NKCC1 protein in the SCN was found to vary significantly over the circadian cycle in hamsters housed in free-running conditions. Overall, NKCC1 protein was greater in the ventral SCN than in the dorsal SCN, although no significant differences were observed across lighting conditions or time of day in either subregion. These data support the hypothesis that NKCC1 protein expression can be regulated by environmental lighting and circadian mechanisms within the SCN.